International Law Has a Role to Play in Addressing Antibiotic Resistance. (2015) - Hoffman, Steven J.; Røttingen, John-Arne; Frenk, Julio
Abstract : Adopting international legal agreements for every global health challenge is not a good idea. Such an enterprise would require unprecedented political mobilization and resources that are impossible to sustain, and it would lead to further fragmentation in global health governance. International legalization also has its costs and trade-offs, including potentially devastating dark sides that we have tallied elsewhere. Yet we believe that calls for an international legal agreement on antibiotic resistance (ABR) are important and that such an agreement is in fact much needed for the future of global health. We came to this conclusion based on a reasoned assessment of the facts before us — the potential benefits, costs, and trade-offs of an ABR legal agreement — and consideration of four criteria we previously proposed for prospectively evaluating proposals for new global health treaties.3 We came to this conclusion despite previously expressing concerns about adopting new international legal agreements on global health issues.